Brazil’s Historians in North America, 1980-2019: A Survey of Their Careers - Kraay, Hendrik (Brasiliana: Journal for Brazilian Studies, 2021)
This article examines the professional careers of the 290 historians who received doctorates in Brazilian history from universities in Canada and the United States between 1980 and 2019. It is a follow-up to a 1990 study by Roderick J. Barman on North American historians of Brazil from 1950 to 1987. While the 1980s were a nadir for the field, historians of Brazil enjoyed unexpectedly good academic career outcomes in the 1990s and early 2000s; they continued to do well in the academic job market, while many of their dissertations were published. The data also reveal some enduring patterns when it comes to the chronological periods and geographical areas on which these historians focus, as well as the rising interest in post-1945 history. The proportion of women winning doctorates has stabilized at levels slightly higher than that of the profession as a whole; however, some small but troubling gender inequities persist.